(untitled) (Eurasian Journal of Ecology, 2016)
Currently the majority of ecosystem services have no economical evaluation that causes mismanagement of natural resources related to pollution of the environment and depletion of its resources – negative externalities. In the article, the possibilities of transition to payments for ecosystem services as the way to build sustainable economy are discussed. It is necessary to provide Kazakhstan’s active involvement in programs that elaborate ecosystem payments schemes at the governmental, regional and local levels for their efficient implication, as well as in international ecosystem services partnership.